(44,44+78,56):12,3-2,3
12,3-x+4,5=2,3
12,3 - x + 4,5 = 2,3
x + 4,5 = 12,3 - 2,3
x + 4,5 = 10
x = 10 - 4,5
x = 5,5
= 5,5
Cach lam
12,3 - x = 2,3 + 4,5
12,3 - x = 6,8
x= 5,5
12 , 3 - x + 4 , 5 = 2 , 3
12 , 3 + 4 , 5 - x = 2 , 3
16 , 8 - x = 2 , 3
x = 14 , 5
12,3 - X + 4,5 =2,3
12,3 - x + 4,5 =2,3
12,3- x =4,5 - 2,3
12,3- x =2,2
x =12,3 + 2,2,
x =14,5
×+4,5=12,3-2,3
×=10-4,5
×=6,5
12,3 - X + 4,5 =2,3
12,3 - X + 4,5 = 2,3
X + 4,5 = 12,3 -2,3
X + 4,5 = 10
X = 10 - 4,5
X = 5,5
12,3-x+4,5=2,3
7,8-x=2,3
x=7,8-2,3
x=5,5
Bài 1: 12,3-x+4,5=2,3
12.3 - x + 4.5 = 2.3
x + 4.5 = 12.3 - 2.3
x + 4.5 = 10
x = 10 - 4.5
x = 5.5
12,3-x+4,5=2,3
X + 4,5 = 12,3 - 2,3
X + 4,5 = 10
X = 10 - 4,5
X= 5,5.
Tìm x
12,3 - x +4,5 =2,3
Tìm x
12,3 - x +4,5 =2,3
12,3-x=2,3-4,5
12,3-x = - 2,2
x =12,3 - (-2,2)
x = 14,5
x=
Giải bằng 2 cách:
12,3 - 4,5 + x = 2,3
12,3 - 4,5 + x = 2.3
=> 7,8 + x = 2,3
=> x = -5,5
12,3 - 4,5 + x = 2,3
=> x = 2,3 - 12,3 + 4,5
=> x = -5,5
Trl :
C1 : 12,3 - 4,5 + x = 2.3
7,8 + x = 2,3
x = - 5,5
C2 : 12,3 - 4,5 + x = 2,3
x = 2,3 - 12,3 + 4,5
x = - 5,5
Cho xin 1 tk nhé mn
B= 12,3 x 5,6 - 5,6 x 2,3 + 8,4 = ?
nhầm rùi
B = 12,3 x 5,6 - 5,6 x 2,3 x 8,4
B = 12,3 x 5,6 - 2,3 x 5,6 + 8,4
B = ( 12,3 - 2,3 ) x 5,6 + 8,4
B = 10 x 5,6 + 8,4
B = 56 + 8,4
B = 64,4
B = 12,3 x 5,6 - 5,6 x 2,3 x 8,4
B = 12,3 x 5,6 - 2,3 x 5,6 + 8,4
B = ( 12,3 - 2,3 ) x 5,6 + 8,4
B = 10 x 5,6 + 8,4
B = 56 + 8,4
B = 64,4
B = 12,3 x 5,6 - 5,6 x 2,3 x 8,4
B = 12,3 x 5,6 - 2,3 x 5,6 + 8,4
B = ( 12,3 - 2,3 ) x 5,6 + 8,4
B = 10 x 5,6 + 8,4
B = 56 + 8,4
B = 64,4
Tìm x biết x nhân 12,3 - x nhân 2,3 =5,6
dấu nhân là dấu . nha ! (ở THCS)
x.12,3 - x.2,3 = 5,6
x. (12,3-2,3) = 5,6
x. 10 = 5,6
x = 5,6 : 10
x = 0,56
12,3 -x + 4,5 +2,3
may ban giup minh voi